Physiological and locomotor variations of 3v3 and 5v5 small-sided games soccer formats: A 4-month study on sedentary young adults - Xu, Qi (2024)
The objectives of this study were twofold: (a) to analyze the variability of 3v3 and 5v5 small-sided games (SSG) formats in sedentary young adults, and (b) to compare the physiological and loco motor demands of 3v3 and 5v5 SSG formats while considering variations based on sex. The study followed a longitudinal design over 4 months. Thirty sedentary young adults with a mean age of 20.2±1.0 years, height of 1.67±0.06 m, and body mass of 86.3±11.8 kg were included in the study. The participants engaged in 3v3 and 5v5 SSG formats, with each format being played 10 times per month. During each session, heart rate (HR), rate of perceived exertion (RPE), and total distance were measured and analyzed. The within-player variability for HR ranged from a minimum of 1.6% to a maximum of 2.8% (considering the levels at each month), while the between-players variability for HR ranged from a minimum of 1.4% to a maximum of 2.6% (considering the levels at each month). Similar variability patterns were observed for the other outcomes. In terms of comparisons between the formats, the 3v3 format resulted in higher RPE than the 5v5 format for both male (p=0.006) and female (p=0.628) participants, as well as for the other outcome measures. In summary, these findings highlight the reproducibility of physiological responses in 3v3 and 5v5 SSG among sedentary individuals. Notably, the 3v3 format consistently induced higher RPE levels. These findings underscore the importance of programming SSG based on sex and format preferences for optimizing exercise outcomes in sedentary.